Anti-aging and antioxidant potential of Paullinia cupana var. sorbilis: findings in Caenorhabditis elegans indicate a new utilization for roasted seeds of guarana - Peixoto, Herbenya; Roxo, Mariana; Röhrig, Teresa; Richling, Elke; Wang, Xiaojuan; Wink, Michael (Medicines, 2017)
Background: Roasted seeds of Amazonian guarana (Paullinia cupana var. sorbilis; Sapindaceae) are popular in South America due to their stimulant activity on the central nervous system (CNS). Rich in purine alkaloids, markedly caffeine, the seeds are extensively used in the Brazilian beverage industry for the preparation of soft drinks and as additives in energy drinks. Methods: To investigate the putative anti-aging and antioxidant activity of guarana, we used the model organism Caenorhabditis elegans. Chemical analyses were performed using high-performance liquid chromatography (HPLC) and electrospray ionization-mass spectrometry (ESI-MS/MS). Results: When tested in the model system Caenorhabditis elegans, the water extract from roasted guarana seeds enhanced resistance against oxidative stress, extended lifespan and attenuated aging markers such as muscle function decline and polyQ40 aggregation. Conclusions: In the current study, we demonstrate that guarana extracts can work as a powerful antioxidant in vivo; moreover, guarana extracts exhibit anti-aging properties. Our results suggest that the biological activities of guarana go beyond the extensively reported CNS stimulation.